(untitled) (Research, Society and Development, 2022)
Leukemia has as its main characteristic the accumulation of leukocytes in the bone marrow and blood, with the classification of the place where it will affect and also the speed of progress of the disease. In terms of the progressive speed of this cancer, it stands out chronic and acute, more common in adults and with a delayed symptomatic manifestation and another more common in children and has about 80% of cure. The diagnosis is made through the signs and symptoms present by the patient and together with the blood count. Studies show that the use of miRNAS in the diagnosis of leukemia has become very promising, mainly because it is a painless, less invasive and safe technique, and can also be used to monitor the status of this neoplasm. As a statism, a study showed the use of these RNA molecules that are used to delay cellular apoptosis, consequently prolonging the quality of life of patients with leukemia. In view of these studies, a survey was carried out between August and October 2022, through a descriptive review and survey in the VHL and Pubmed databases, with the purpose of analyzing the profile of miRNAs present in AML and CML, allowing the distinction in the subtypes and degrees, as its association with the diagnosis, prognosis and therapeutic efficacy